Photobase generators derived from trans‐o‐coumaric acid for anionic UV curing systems without gas generation. Issue 10 (3rd March 2015) - Arimitsu, Koji; Takemori, Yuri; Nakajima, Atsushi; Oguri, Ayaka; Furutani, Masahiro; Gunji, Takahiro; Abe, Yoshimoto
<x xml:space="preserve">Abstract</x> Anionic UV curing systems of poly(glycerol methacrylate) and/or poly[3‐(methacryloyloxy)propyltrimethoxysilane] are obtained using novel photobase generators (PBGs) derived from trans‐o‐coumaric acid. These PBGs decompose into amines and coumarins by UV irradiation without generation of gases that cause cracks and bubbles in cured films. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>